Computer-assisted instruction versus inquiry-based learning: The importance of working memory capacity - Chevalère, Johann; Cazenave, Loreleï; Berthon, Mickaël; Martinez, Ruben; Mazenod, Vincent; Borion, Marie-Claude; Pailler, Delphine; Rocher, Nicolas; Cadet, Rémi; Lenne, Catherine; Maïonchi-Pino, Norbert; Huguet, Pascal (PLOS ONE, 2021)
The Covid-19 pandemic has led millions of students worldwide to intensify their use of digital education. This massive change is not reflected by the scant scientific research on the effectiveness of methods relying on digital learning compared to other innovative and more popular methods involving face-to-face interactions. Here, we tested the effectiveness of computer-assisted instruction (CAI) in Science and Technology compared to inquiry-based learning (IBL), another modern method which, however, requires students to interact with each other in the classroom. Our research also considered socio-cognitive factors–working memory (WM), socioeconomic status (SES), and academic self-concept (ASC)–known to predict academic performance but usually ignored in research on IBL and CAI. Five hundred and nine middle-school students, a fairly high sample size compared with relevant studies, received either IBL or CAI for a period varying from four to ten weeks prior to the Covid-19 events. After controlling for students’ prior knowledge and socio-cognitive factors, multilevel modelling showed that CAI was more effective than IBL. Although CAI-related benefits were stable across students’ SES and ASC, they were particularly pronounced for those with higher WM capacity. While indicating the need to adapt CAI for students with poorer WM, these findings further justify the use of CAI both in normal times (without excluding other methods) and during pandemic episodes.